Hijrah and changing religious preferences in contemporary Islamic legal practice - Imam Mustofa; Muhammad Iqbal Juliansyahzen; Wildani Hefni (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2023)
This research examines how urban Muslim communities in Purwokerto understand and practice religion in the area of muamalah (social relationships between people). Religious practice in urban Muslim communities is different from other religious communities. The intersection between the reality of modernity, Islamicity, and identity provides a model for distinguishing contemporary Muslim religious practices. This study is based on field research employing a phenomenological approach. Participatory observation was used to collect data from two mosques in Purwokerto City: the General Soedirman Grand Mosque and the Gelora Indah Mosque. Both mosques serve as the hub of religious discourse for Purwokerto's urban Muslim community, and they host a variety of religious studies on a regular basis. In-depth interviews were performed with worshippers from the two mosques by the researchers. Secondary data is derived from studies, journals, books, and other sources. This article concludes that urban Muslim identity is manifested in the shift away from usury practices and the choice of halal products. Studies in urban mosques and social media cannot isolate the rhetoric from the social formation of urban Muslims. In this environment, hijrah (shifting paradigm) has emerged as one of the trends that give rise to new nuances and views of any Islamic legal concept that is an annotated version of older works. Because of these shifts in preferences, the discipline of Islamic law, particularly fiqh muamalah, has become one of the most important areas for the expression of religious experience in the lives of urban Muslims